Akulturasi Budaya Islam-Jawa dalam Pementasan Kesenian Ketoprak - Bagus Wahyu Setyawan (Dance and Theatre Review, 2019)
The purpose of this study was to describe the form of acculturation of Javanese-Islamic culture in ketoprak performance. The acculturation of Javanese-Islamic culture can be found in a variety of Egyptian-style of ketoprak. The Egyptian’s ketoprak is often referred to as Ketoprak Baghdad, Ketoprak Stambul, and Ketoprak 1001 nights because the performed stories are from the Middle East (the story of 1001 nights). The acculturation of Islamic-Javanese culture in the Egyptian’s ketoprak can be seen in terms of stories that adopt the plays from the Middle East or the play of 1001 nights. Besides, the acculturation of Islamic-Javanese culture also appears in terms of costumes and accompaniment. The costumes used are different from Ketoprak in general, which is a combination of Javanese costume and Middle Eastern style clothing. In terms of accompaniment, the Egyptian style of ketoprak also uses “terbang” musical instruments by bringing in the Islamic nuances of songs. In today’s era, Islamic nuances of ketoprak are used in any activities related to ceremonies and commemorations of Islamic holidays. Therefore, the development of ketoprak in the present has become more flexible and adapted to the needs of the community.Keywords: acculturation; Islamic-Javanese culture; the Egyptian style; Ketoprak; Islamic nuances